2022
DOI: 10.7554/elife.80901
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the HOPS tethering complex, a lysosomal membrane fusion machinery

Abstract: Lysosomes are essential for cellular recycling, nutrient signaling, autophagy, and pathogenic bacteria and viruses invasion. Lysosomal fusion is fundamental to cell survival and requires HOPS, a conserved heterohexameric tethering complex. On the membranes to be fused, HOPS binds small membrane-associated GTPases and assembles SNAREs for fusion, but how the complex fulfills its function remained speculative. Here, we used cryo-electron microscopy to reveal the structure of HOPS. Unlike previously reported, sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 88 publications
0
44
0
Order By: Relevance
“…We previously proposed that HOPS may engage directly with ZF5.3 to promote escape during vesicle fusion; it may also promote trafficking into intraluminal vesicles as a prerequisite to endosomal escape . The observation that the high nuclear delivery efficiency of ZF5.3- t MeCP2 depends on both HOPS and CORVET, favors the former explanation and deserves further study, especially as HOPS and CORVET share 4 of 6 subunits in common. , Identification of those molecular features that promote productive interaction with HOPS and/or CORVET could improve the efficiency of other delivery strategies, including lipid nanoparticles, whose efficiency remains <10% …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We previously proposed that HOPS may engage directly with ZF5.3 to promote escape during vesicle fusion; it may also promote trafficking into intraluminal vesicles as a prerequisite to endosomal escape . The observation that the high nuclear delivery efficiency of ZF5.3- t MeCP2 depends on both HOPS and CORVET, favors the former explanation and deserves further study, especially as HOPS and CORVET share 4 of 6 subunits in common. , Identification of those molecular features that promote productive interaction with HOPS and/or CORVET could improve the efficiency of other delivery strategies, including lipid nanoparticles, whose efficiency remains <10% …”
Section: Resultsmentioning
confidence: 97%
“…A class C core vacuole/ endosome tethering (CORVET) complex facilitates the fusion of Rab5 positive early endosomes, while the fusion of Rab7 positive late endosomes to lysosomes requires the homotypic fusion and protein sorting (HOPS)-tethering complex. 60,61 Previous mechanistic studies indicate that efficient cytosolic and nuclear trafficking of ZF5.3 relies on the HOPS complex, but not the analogous CORVET complex. 15 We thus sought to investigate if this dependence also held for the ZF5.3 conjugate of tMeCP2.…”
Section: Design Purification and Characterization Of Mecp2mentioning
confidence: 99%
See 1 more Smart Citation
“…Although CATCHR and HOPS/CORVET-family MTCs were long thought to be conformationally variable, single-particle cryo-EM studies of exocyst 11 , HOPS 62 , and now Dsl1:Qb:Qc have revealed relatively rigid cores with widely separated membrane-binding sites. It may instead be the attachments formed between MTCs and membranes that are flexible.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the C-terminal CNH domain has a β-propeller structure that binds to the small GTPase Rap2 [ 2 ]. Recently, the structures of the CNH domain, which has the homologous function of binding small GTPases, were elucidated [ 36 , 37 ]. The CNH domain of TNIK is separated from the kinase domain and subsequent helices by an approximately 500-residue unstructured region.…”
Section: Structural Model Of Full-length Tnik Indicates Scaffold Func...mentioning
confidence: 99%